THE ROLE OF ONLINE ACTIVITIES WHILE TEACHING FOREIGN LANGUAGES FOR B2 LEVEL LEARNERS - N.Muhammadjonova (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation. This article examines the significance of online activities in teaching foreign languages to B2 level learners. With the increasing availability of digital tools, online platforms, and interactive technologies, foreign language instruction has expanded beyond traditional classroom settings. The study highlights how online activities support the acquisition of advanced language skills, enhance learner autonomy, promote authentic communication, and facilitate collaborative learning. The article further discusses challenges and offers methodological recommendations for effective integration of online activities in B2-level language instruction.